Press Manipulation and Its Negative Impact on the Youth - Manea, Ioana; Popa, Ioana (Studies and Scientific Researches. Economics Edition, 2010)
Nowadays, manipulation may be regarded as an essential instrument of the “mass industrial society”, aiming at the conclusion of certain agreements that are convenient to the issuing party, turning to deceit with falsified arguments, as well as to appeals to emotional or non-rational components. The particular forms that it takes in various fields of social life may be found anywhere, from the political form to the economic one. Press strategies have the capacity of manipulating the young consumer’s behaviour, generating numerous negative effects on their everyday life.